INOVASI MOBILE DIGITAL VIDEO RECORDER (MDVR) MENGURANGI RISIKO KECELAKAAN TAMBANG NIKEL PT PPA - Ashthofi Zainati; Rayhan Fadhillah; Fikri Fahmi Amrulloh3; Sukardi Yusuf (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2025)
The mining industry faces a high risk of work-related accidents, often caused by fatigue and lack of supervision. PT Putra Perkasa Abadi (PPA), which experienced a fatigue-related incident in 2023, implemented the